Wind energy - the facts : a guide to the technology, economics and future of wind power. - European Wind Energy Association EWEA (London : Earthscan, 2009)
Wind power is often held up as the most accessible and cost effective route to reducing our reliance on fossil fuels and improving our energy independence, yet knowledge of what it offers is often clouded by myths and misunderstandings, which can hamper its adoption. This new book, the result of an ambitious project coordinated by the European Wind Energy Association, presents the facts about wind energy. It includes six sections discussing: technology; grid integration; economics of wind; industry and markets; environmental impacts; scenarios and targets. Contributions are drawn from nine leading research bodies across Europe, and the material is global in its scope. It is therefore an essential resource and reference for those whose work or study demands an in-depth examination of the subject, and for anyone who wants detailed, accurate and up-to-date information on this key energy source.